2000
DOI: 10.1007/s004240000414
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the large-conductance Ca-activated K channel in myocytes of rat saphenous artery

Abstract: We used the patch-clamp method to characterize the BK channel in freshly isolated myocytes from the saphenous branch of the rat femoral artery. Single-channel recordings revealed that the BK channel had a conductance of 187 pS in symmetrical 150 mM KCl, was blocked by external tetraethylammonium (TEA) with a KD(TEA) of approx. 300 microM at +40 mV, and by submicromolar charybdotoxin (CTX). The sensitivity of the BK channel to Ca was especially high (KD(ca) approx. 0.1 microM at +60 mV) compared to skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
3
5
0
Order By: Relevance
“…The resulting slope factors resemble those reported for cloned dog BK channels expressed in human embryonic kidney cells (15.1 mV, α subunit alone compared to 14–15 mV in this study) [33] and oocytes (11.9–14.1 mV, α + β1 subunits) [34] and do not differ from those observed by other investigators in resistance cerebral arteries from rats (14–16 mV) [35, 36]. Additionally, investigators have found close agreement between the macroscopic methods employed here to determine BK voltage dependency and estimates from single-channel records from the same arterial tissue [11, 34]. …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The resulting slope factors resemble those reported for cloned dog BK channels expressed in human embryonic kidney cells (15.1 mV, α subunit alone compared to 14–15 mV in this study) [33] and oocytes (11.9–14.1 mV, α + β1 subunits) [34] and do not differ from those observed by other investigators in resistance cerebral arteries from rats (14–16 mV) [35, 36]. Additionally, investigators have found close agreement between the macroscopic methods employed here to determine BK voltage dependency and estimates from single-channel records from the same arterial tissue [11, 34]. …”
Section: Discussionsupporting
confidence: 68%
“…To minimize this, K + was lowered and replaced with choline. This method has been employed by other investigators when examining BK current voltage dependency [11]. Standard intracellular solution consisted of (in m M ): KCl 20, choline-Cl 120, MgCl 2 1.5, CaCl 2 2.65, EGTA 5, HEPES 5, glucose 5, pH 7.2 with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…Blocking polyamine synthesis with the ornithine decarboxylase inhibitor DFMO (difluoromethylornithine) released BK channel rectification supporting the notion of a rectifying action imposed by polyamines. Similar data were reported for BK channels in myocytes from the saphenous branch of the rat femoral artery (Catacuzzeno et al, 2000). These discoveries remind to the mechanism of current rectification caused by polyamines at inward rectifier channels (K ir ) (Fakler et al, 1995).…”
Section: Bk Channels -And Polyaminessupporting
confidence: 83%
“…These results indicate that an increase of [K ϩ ]o in the physiological range (6-12 mM) inhibits [Ca 2ϩ ]i increase in endothelial cells and diminishes EDR by depolarizing the membrane potential, decreasing K ϩ efflux, and activating the Na ϩ -K ϩ pump, thereby modulating the release of endothelium-derived vasoactive factors from endothelial cells and vasomotor tone. (5,7,29). This activation, in turn, induces an efflux of intracellular K ϩ .…”
mentioning
confidence: 99%